Imaging metabolism in action. (December 2021) - Green, Felicia; Simmonds, Anna
Abstract : From improving the sensitivity of ion sources to boosting image resolution, Felicia Green and Anna Simmonds unveil the ambitious biological mass spectrometry programme at the Rosalind Franklin Institute to image molecular interactions in tissues.